Significance of PR3-ANCA positivity in eosinophilic granulomatosis with polyangiitis (Churg-Strauss). (21st December 2020) - Papo, Matthias; Sinico, Renato A.; Teixeira, Vítor; Venhoff, Nils; Urban, Maria-Letizia; Iudici, Michele; Mahrhold, Juliane; Locatelli, Francesco; Cassone, Giulia; Schiavon, Franco; Seeliger, Benjamin; Neumann, Thomas; et al.
Abstract: Objectives: Only a third of patients with eosinophilic granulomatosis with polyangiitis (EGPA) are ANCA-positive, mainly directed against MPO. ANCA directed against PR3 are rarely found in EGPA. We aimed to examine the significance of PR3-ANCA in EGPA. Methods: We set up a retrospective European multicentre cohort including 845 patients. Baseline characteristics and outcomes were analysed and compared according to ANCA status. Results: ANCA status was available for 734 patients: 508 (69.2%) ANCA-negative, 210 (28.6%) MPO-ANCA and 16 (2.2%) PR3-ANCA. At baseline, PR3-ANCA patients, compared with those with MPO-ANCA and ANCA-negative, less frequently had active asthma (69% vs 91% and 93%, P  = 0.003, respectively) and peripheral neuropathy (31% vs 71% and 47%, P  < 0.0001), more frequently had cutaneous manifestations (63% vs 38% and 34%, P  = 0.03) and pulmonary nodules (25% vs 10% and 8%, P  = 0.046), and lower median eosinophil count (1450 vs 5400 and 3224/mm 3, P  < 0.0001). Vasculitis relapse-free survival was shorter for PR3-ANCA (hazard ratio 6.05, P  = 0.005) and MPO-ANCA patients (hazard ratio 1.88, P  = 0.0002) compared with ANCA-negative patients. Conclusion: PR3-ANCA EGPA patients differ from those with MPO-ANCA and negative ANCA, and share clinical features with granulomatosis with polyangiitis. This suggests that PR3-ANCA EGPA could be a particular form of PR3-ANCA-associated vasculitis.